QUALITY BY DESIGN-BASED OPTIMIZATION AND VALIDATION OF NEW REVERSE PHASE-HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR SIMULTANEOUS ESTIMATION OF LEVOFLOXACIN HEMIHYDRATE AND AMBROXOL HYDROCHLORIDE IN BULK AND ITS PHARMACEUTICAL DOSAGE FORM - m, Sumithra; P, Shanmugasundaram; V, Ravichandiran (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Innovative application of quality by design (QbD) technique for simultaneous estimation of levofloxacin and ambroxol hydrochloride (HCL) in bulk and its pharmaceutical dosage form using reverse phase-high-performance liquid chromatography (RP-HPLC) method. Method: A method has been developed for the separation of levofloxacin and ambroxol HCL using RP-HPLC on C18 column (250 4.6 mm, 5 ml) with ultraviolet detection at 306 nm. Experimental designs were applied for multivariate optimization of the experimental conditions of RP-HPLC method. Three independent factors: Acetonitrile content in the mobile phase composition, buffer pH, and flow rate were used to design mathematical models. Here, central composite design (CCD) experimental design was used to study the response surface technique and to study in depth the effects of these independent factors. Derringer's desirability function was applied to simultaneously optimize the retention time of last eluting peak (ambroxol hydrochloride) and resolution between levofloxacin and ambroxol hydrochloride. Result and Discussion: The predicted optimum assay condition consisted of acetonitrile, potassium dihydrogen phosphate buffer (pH 5.00; potassium dihydrogen phosphate), and methanol in a proportion of 20:70:10% v/v, respectively, as the mobile phase at a flow rate of 1.2 ml/minute. Using this optimum condition, baseline separation of both drugs with good resolution and a run time of <5 minutes were achieved. The optimized assay condition was validated according to the ICH guidelines to confirm specificity, linearity, accuracy, and precision. Keywords: Levofloxacin, Ambroxol hydrochloride, Experimental design, Response surface methodology, Derringer's desirability, Quality by design approach.